Przeciw dziennikarskiej „pańszczyźnie”. Proza Tadeusza Nowakowskiego - Szadkowska, Ewelina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article presents a theme of art and artist, contained in novels and short stories of Tadeusz Nowakowski. The protagonists of his prose are the journalists and – at the same time – unrealised writers. They are depended on despotic boss and have no time to write artistic prose. Relations between fiction and biography of Nowakowski enable to identify (obviously, not quite fully) the characters with its empirical author. Nowakowski perceives this space of his creative activity as a substitute for autobiography.